2012
DOI: 10.1614/ws-d-11-00172.1
|View full text |Cite
|
Sign up to set email alerts
|

How Important are Crop Spatial Pattern and Density for Weed Suppression by Spring Wheat?

Abstract: Previous research has shown that both the density and spatial pattern of wheat have an influence on crop growth and weed suppression, but it is not clear what degree of uniformity is necessary to achieve major improvements in weed suppression. Field experiments were performed over 3 yr to investigate the effects of crop density and different spatial distributions on weed suppression. The spatial pattern of spring wheat sown in five patterns and three densities in small weed-infested plots were analyzed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 27 publications
1
39
1
4
Order By: Relevance
“…Crop spatial pattern is another agronomic factor that can affect grain yield and crop competitiveness against weeds (Olsen et al, 2012). It has been suggested that uniform planting pattern increases the spatial uniformity in leaf area index (LAI), reduces mutual shading, and hastens canopy closure, all of which result in increased radiation interception (RI) by the canopy (Olsen & Weiner, 2007) and increased crop growth and yield (Mashingaidze et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop spatial pattern is another agronomic factor that can affect grain yield and crop competitiveness against weeds (Olsen et al, 2012). It has been suggested that uniform planting pattern increases the spatial uniformity in leaf area index (LAI), reduces mutual shading, and hastens canopy closure, all of which result in increased radiation interception (RI) by the canopy (Olsen & Weiner, 2007) and increased crop growth and yield (Mashingaidze et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers (Weiner et al, 2001;Olsen & Weiner, 2005;Olsen et al, 2012;Dusabumuremyi et al, 2014) noted that increased crop uniformity had a negative effect on weed biomass. However, some other researchers (Teasdale, 1995;Westgate et al, 1997) reported that crop growth and yield does not always increase in narrow-row planting.…”
Section: Introductionmentioning
confidence: 99%
“…A narrow row spacing of 15 cm was reported to perform better in suppressing P. minor compared with the 23 cm spacing (Mahajan et al, 2004). Though the effectiveness of reduced row spacing on weed control depends on several other factors, including water limitations, nutrient placement, ratio between crop to weed height, and timing of emergence of crops and weeds, several recent studies have shown increased uniformity can help in reducing weed biomass as well as increasing yields in a variety of crops (Weiner et al, 2001;Olsen et al, 2012;Marin and Weiner, 2014).…”
Section: Spatial Arrangement Of the Cropmentioning
confidence: 99%
“…The use of these machines is increasing because manual transplanting is a labour intensive operation in the cultivation of rice. At the same time, previous studies have shown that crop spatial pattern can affect crop growth, grain yield and herbicide efficacy (OLSEN et al, 2012, OLSEN et al, 2005, WEINER et al, 2001. A recent study, Olsen et al (2012) observed that increased crop uniformity had a negative effect on weed biomass, and concluded that crop pattern effects on weeds occur only through size-asymmetric competition.…”
Section: Introductionmentioning
confidence: 98%
“…At the same time, previous studies have shown that crop spatial pattern can affect crop growth, grain yield and herbicide efficacy (OLSEN et al, 2012, OLSEN et al, 2005, WEINER et al, 2001. A recent study, Olsen et al (2012) observed that increased crop uniformity had a negative effect on weed biomass, and concluded that crop pattern effects on weeds occur only through size-asymmetric competition. Olsen et al (2005) have shown that a highly uniform pattern of wheat plants suppresses weeds 30% better than plants distributed in row pattern.…”
Section: Introductionmentioning
confidence: 98%